HUBUNGAN ANTARA REGULASI DIRI DENGAN KESEPIAN PADA MAHASISWA TAHUN PERTAMA DI FAKULTAS KESEHATAN MASYARAKAT DAN FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS DIPONEGORO SEMARANG - Ningrumsari, Putri Ria (Jurnal EMPATI, 2017)
Individuals in early adult experience transition from high school to college. At that time involves major changes in the physical, cognitive, and psychosocial aspects. During the transition to college, it was found that there was a risk of a lonely phenomenon. This reasearch aims to determine the relationship between self-regulation with loneliness in first year students in the Faculty of Public Health and Faculty of Social and Political Sciences Diponegoro University of Semarang. The population of this reasearch is the first year students in the Faculty of Public Health and Faculty of Social and Political Sciences Diponegoro University numbered 886 students. The sample of research was 248 people obtained with convenience sampling technique. The data were collected using Self Regulation Scale (26 valid items; Î± = .88) and Loneliness Scale (26 valid items; Î± = .89), which have been tested on 92 students. Simple regression analysis showed a negative and significant relationship between self-regulation with loneliness shown through rxy = -.54 correlation coefficient with p = .000 (p <.001). The higher the self-regulation, the loneliness felt will be lower, and vice versa. Self regulation provides an effective contribution of 29% on loneliness. Additional analysis in this study used an independent sample t-test, which showed that there was no significant difference in loneliness based on differences in residence, gender, and the origin of the faculty. This research is expected to be a consideration for students and faculty about self regulation and loneliness, as well as supporting references for further researchers.Â Â Â